Achilles tendon thickness is associated with coronary lesion severity in acute coronary syndrome patients without familial hypercholesterolemia. Issue 2 (February 2022) - Fujiwara, Ryosuke; Yahiro, Ryosuke; Horio, Takeshi; Miyauchi, Masafumi; Yoshimura, Ryutaro; Matsuoka, Yujiro; Yokouchi, Go; Sakamoto, Yuya; Matsumoto, Naoki; Fukuda, Kohei; Izumiya, Yasuhiro; Yoshiyama, Minoru; et al.
Highlights: Clinical significance of mild thickening of Achilles tendon is unclear. Achilles tendon thickness (ATT), even though its level was <9 mm, was associated with coronary lesion severity in patients with early-onset acute coronary syndrome. Apart from diagnosing familial hypercholesterolemia, ATT may be a predictor of the progression of coronary artery disease. Abstract: Background: Thickening of Achilles tendon (≥9 mm on radiography) is one of the diagnostic criteria for familial hypercholesterolemia (FH). Since FH is associated with premature coronary artery disease (CAD) including acute coronary syndrome (ACS), measurement of Achilles tendon thickness (ATT) is important for early diagnosis of FH. However, clinical significance of mild thickening of Achilles tendon in non-FH patients with CAD is unclear. The present study investigated the association of ATT with coronary lesion severity in early-onset ACS without clinically diagnosed FH. Methods: From outpatients who had a history of ACS under 60 years old, 76 clinically non-FH subjects (71 men and 5 women; mean age at the onset of ACS, 50.5 years) with maximum ATT of <9 mm were enrolled in this study. The severity of coronary lesions was assessed by SYNTAX score derived from coronary angiography at the onset of ACS. Results: ATT levels were not significantly different among patients with ST-elevation myocardial infarction (STEMI, n=47), non-STEMI (n=12), and unstable angina (n=17). Whereas, both average and maximum ATT were significantly larger in patients with multivessel lesions (n=25) than in those with single-vessel disease (n=51). Furthermore, SYNTAX score was positively correlated with average ATT (r=0.368, p =0.0011) and maximum ATT (r=0.388, p =0.0005). As for the relation to clinical parameters, maximum ATT had positive correlations with body mass index and C-reactive protein. A multiple regression analysis revealed that average and maximum ATT were significantly associated with SYNTAX score, independently of various confounding factors. Conclusions: Our findings demonstrated that ATT, even though its level was <9 mm, was associated with coronary lesion severity in clinically non-FH patients with early-onset ACS. Apart from diagnosing FH, ATT may be a predictor of the progression of CAD. Graphic abstract: Image, graphical abstract